2005
DOI: 10.1097/01.gim.0000177531.53338.65
|View full text |Cite
|
Sign up to set email alerts
|

Patient acceptability of genotypic testing for hemochromatosis in primary care

Abstract: Purpose: Genetic screening can enable timely detection and treatment of hereditary hemochromatosis (HH). Little is known about patient acceptability of DNA testing as compared to conventional phenotypic testing. Methods:Within the HEIRS Study, a large primary-care screening study of HH and iron overload, we randomly assigned participants to receive brief information on either HH genotypic or phenotypic testing, and assessed the willingness to accept this test. The study was designed to recruit an equal number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
(34 reference statements)
3
11
0
Order By: Relevance
“…A recent meta-analysis [78] reviewed only 3 small cohorts and, although the evidence was limited, concluded that there is no demonstrable rise in anxiety levels or decrease in quality-of-life scores following testing. This concurs with population screening studies, which have found both genotypic and phenotypic methods to be acceptable and producing no evidence of psychological disturbance [79,80].…”
Section: Diagnosis and Screeningsupporting
confidence: 85%
“…A recent meta-analysis [78] reviewed only 3 small cohorts and, although the evidence was limited, concluded that there is no demonstrable rise in anxiety levels or decrease in quality-of-life scores following testing. This concurs with population screening studies, which have found both genotypic and phenotypic methods to be acceptable and producing no evidence of psychological disturbance [79,80].…”
Section: Diagnosis and Screeningsupporting
confidence: 85%
“…Cadet et al attributed the effectiveness of this reverse cascade screening program largely to a dedicated genetic counseling program, accessible medical information, and pre-established protection from insurance discrimination. In the Hemochromatosis and Iron Overload Screening Study (HEIRS), patient education regarding the nature of HFE testing, the importance of disease detection, and privacy protection was an essential factor for achieving high rates of screening participation [58].…”
Section: Discussionmentioning
confidence: 99%
“…15 A factor analysis of this scale indicated that all nine "worry " items loaded on this single scale, with high internal consistency (alpha of Ͼ.90). The nine health worry items included (1) worry about risk of developing IO or hemochromatosis, (2) thoughts about test results caused problems in work or home life, (3) feeling frustrated that no known mutations have been found to explain IO, (4) worry about confidentiality of test results, (5) feeling that people don't think you're as good as they are, (6) worry about risk to family members, (7) having problems enjoying life because of test results, (8) feeling loss of control because of test results, (9) feeling upset, sad or anxious about test results. Answers range from 1 to 4 where 1 ϭ Never, 2 ϭ Rarely, 3 ϭ Sometimes, and 4 ϭ Often.…”
Section: Health Worrymentioning
confidence: 99%
“…2 Although populationbased HFE screening may be a justifiable way to identify individuals at risk, it is important to evaluate screening risks and benefits, including the impact of an HFE screening program on psychosocial status or quality of life. 3,4 Previous studies examining acceptability of genetic testing for hemochromatosis note HFE genotyping is acceptable to many 5 or even most 6 individuals offered testing, and studies have not shown deleterious psychosocial outcomes. [7][8][9] This has led to a preliminary conclusion that population-based screening should not be discouraged on the basis of potential adverse psychosocial effects.…”
mentioning
confidence: 99%